Harmonic Vectors: essay for a systematics of harmonic progressions (Orfeu, 2017)
This is a Portuguese version of what itsauthor, Belgian musicologist Nicolas Meeùs (1944-), considered to be the foundingessay for his theory of harmonic vectors.In it, Meeùs revisits the discussion of theclassification of harmonic progressions,reviews the arguments of three of the 20thcentury’s most important music theorists,namely Hugo Riemann, Heinrich Schenker,and Arnold Schoenberg, and acknowledges the contributions of earlier theoreticians, such as Jean-Philippe Rameau, Gottfried Weber, Anton Bruckner, and SimonSechter. The author also dialogues with hiscontemporary Yitzhak Sadai’s then-recentsystematization, published in 1980. Finally,Meeùs applies vector analysis to works of J.S. Bach, Beethoven, and Chopin to illustrate his thesis that it is possible to reduce thesyntax of harmonic progressions to twocategories, the “vecteur dominant” and the“vecteur sous-dominant”. This translationof the French original, published in 1988in Fascicules d’Analyse Musicale, receivedsome annotations by the present authors.
Keywords: Musical Theory and Analysis; Harmonic Progressions; Nicolas Meeùs